2021
DOI: 10.3390/electronics10192443
|View full text |Cite
|
Sign up to set email alerts
|

DWSA: An Intelligent Document Structural Analysis Model for Information Extraction and Data Mining

Abstract: The structure of a document contains rich information such as logical relations in context, hierarchy, affiliation, dependence, and applicability. It will greatly affect the accuracy of document information processing, particularly of legal documents and business contracts. Therefore, intelligent document structural analysis is important to information extraction and data mining. However, unlike the well-studied field of text semantic analysis, current work in document structural analysis is still scarce. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…For the semantic similarity measuring task, constant weighting assumption-based semantic similarity [45] measure between two concepts/words holds better performance for the semantic representation of the concept/words but holds the same weighting relevance. Later, it found that the weight propagation mechanism [46,47] for augmenting input with semantic information achieves desired performance and removes the same weighting curse for concepts/words. Recently, Liu J. et el.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For the semantic similarity measuring task, constant weighting assumption-based semantic similarity [45] measure between two concepts/words holds better performance for the semantic representation of the concept/words but holds the same weighting relevance. Later, it found that the weight propagation mechanism [46,47] for augmenting input with semantic information achieves desired performance and removes the same weighting curse for concepts/words. Recently, Liu J. et el.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The traditional teaching approaches, such as lectures and group discussions, were blamed for the student's poor academic performance in technical drawing. Interactive teaching techniques are one of the tried-and-true approaches to prevent children from performing poorly in school and to increase their enthusiasm for learning [18], [19]. In order to determine how an intelligent tutoring system based on the Web influenced student achievement and interest in technical drawing in Niger State, Nigeria.…”
Section: Introductionmentioning
confidence: 99%